PENGARUH PEMBERIAN AIR REBUSAN DAUN ALPUKAT (Persea americana Mill.) TERHADAP TEKANAN DARAH PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS II DENPASAR SELATAN - Sulistiawati, Anak Agung Ari Novia; Prapti, Ni Ketut Guru; Lestari, Made Pande Lilik (Coping: Community of Publishing in Nursing; Vol 3 No 3 (2015): JURNAL EDISI SEPTEMBER-DESEMBER 2015, 2015)
Hypertension is an escalation of systolic blood pressure > 140 mmHg and diastolic blood pressure > 90 mmHg, on twice measurements after five minutes on a good rest. Hypertension treatment can use pharmacological and non-pharmacological. Boiled avocado leaves-water is one of non-pharmacological treatments. This research aims to find out the effect of boiled avocado leaves-water on blood pressure of hypertension patients using a quasi experimental design, pretest-posttest with control group which are being implemented on 30 samples that have been chosen with purposive sampling method. Data collection have been done by interviewing the respondents about characteristic and measured their blood pressure with a digital spygmomanometer. The result is it was successfully figured out a value of p=0,000 on systolic and diastolic blood pressure, it means there were significant reduction of systolic and diastolic blood pressure of the respondents. The other 15 samples on control group had value of p=0,027, it means there were differences on systolic blood pressure of pretest and posttest which influenced by life style of the respondents during the research. But, the diastolic blood pressure had value of p=0,571 which means there were no any differences during the pretest or posttest of the control group. According to the Independent Sample T-test trials, there were value of p=0,000 which means that boiled Avocado leaves-water influenced the blood pressure of hypertension patients. Based on this research, it is recommended to all nurses to implement the boiled avocado leaves-water to medicate hypertension in complementary way.
Keywords: Blood Pressure, Boiled Avocado Leaves-Water, Hypertension